Analysis and Design Web-Based Computer Service Management Information System - Prayoga Kurniawan; Verri Kuswanto (Komunitas Dosen Indonesia, 2025)
Computer systems are essential to modern business operations but often encounter issues such as slow performance, system crashes, and virus infections due to inadequate maintenance practices. Although computer repair service companies are available to address these problems, they frequently experience inefficiencies caused by limited information about hardware or software damage, poor communication between technicians, and ineffective service reporting systems. These issues reduce the overall quality of service and customer satisfaction. To overcome these challenges, this study developed a web-based service management system designed to streamline repair workflows, enhance coordination among technicians, and improve communication with customers. The system integrates a diagnostic module that applies a simplified Backward Chaining reasoning method, enabling users to identify the causes of computer faults by testing possible hypotheses based on observed symptoms similar to the reasoning process of an expert technician. The system was evaluated using the Blackbox testing method, focusing on input accuracy, feature functionality, and overall system performance. The testing results showed that all system features operated correctly (100%), and the diagnostic module effectively simulated expert reasoning in identifying computer faults. User feedback also indicated noticeable improvements in operational efficiency, technician collaboration, and customer satisfaction. Overall, the proposed system demonstrates its potential as a reliable tool for optimizing computer repair business processes, improving diagnostic accuracy, and enhancing communication and service delivery